2020
DOI: 10.1111/jdv.16874
|View full text |Cite
|
Sign up to set email alerts
|

Delayed melanoma diagnosis in the COVID‐19 era: increased breslow thickness in primary melanomas seen after the COVID‐19 lockdown

Abstract: For Malignant Melanoma (MM), the Breslow thickness and the presence of ulceration are important elements for determining the staging and prognosis 1 . Skin cancer screening and dermoscopic examination allowed an earlier recognition of cutaneous MM, causing especially an over‐detection of thin lesions, without a proportional decline in later‐stage disease 2 . Furthermore, the incidence of thicker MMs does not seem to be decreasing 3;4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
71
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 5 publications
14
71
3
10
Order By: Relevance
“…17 Moreover, studies from Italy showed a statistically significant increase in mean Breslow thickness during the post-lockdown phase compared with the pre-lockdown and decreased detection of melanoma during the COVID-19 pandemic. 18,19 Another study from the United Kingdom has reported that the NMSCs excised in 2020 required significantly larger and more complex surgery than in 2019. 20 Altogether, these findings suggest an increased delay in the diagnosis of skin cancers, which in turn might result in more advanced disease requiring more complex surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, studies from Italy showed a statistically significant increase in mean Breslow thickness during the post-lockdown phase compared with the pre-lockdown and decreased detection of melanoma during the COVID-19 pandemic. 18,19 Another study from the United Kingdom has reported that the NMSCs excised in 2020 required significantly larger and more complex surgery than in 2019. 20 Altogether, these findings suggest an increased delay in the diagnosis of skin cancers, which in turn might result in more advanced disease requiring more complex surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent report from the United Kingdom has shown a decrease up to 47% in the number of non‐melanoma skin cancer treated and melanoma patients undergoing sentinel lymph node biopsies 17 . Moreover, studies from Italy showed a statistically significant increase in mean Breslow thickness during the post‐lockdown phase compared with the pre‐lockdown and decreased detection of melanoma during the COVID‐19 pandemic 18,19 . Another study from the United Kingdom has reported that the NMSCs excised in 2020 required significantly larger and more complex surgery than in 2019 20 .…”
Section: Discussionmentioning
confidence: 99%
“…melanoma or squamous cell carcinoma) and data was incomplete [ 2 ]. One institutional series from Italy suggested diagnostic delay for melanoma, though generalizability is limited given the narrow population coverage [ 3 ]. We hypothesized that the impact on skin cancer care in a Canadian population-level sample would be substantial, with potential differences between skin cancer types and some patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…Curiosamente, no se ha evidenciado que retrasos por causa médica o demoras en la cirugía durante el confinamiento sean causa de tumores de mayor tamaño. Existen trabajos de un único centro con resultados similares tanto en nuestro país 7 como en otros países como Italia 8 .…”
unclassified